Some aspects of biology and exploitation of the green tiger prawn, Penaeus (Penaeus) semisulcatus de Haan from Mandapam (Palk Bay) and Pamban (Gulf of Mannar), southeast coast of India - Maheswarudu, G; Manickam, P E Sampson; Rao, P Vedavyasa; Arputharaj, M R; Muniyandi, K (Indian Journal of Fisheries, 2011)
The results of the exploitation of Penaeus (Penaeus) semisiiicaliis by the Mandapam-based smallmechanized vessels and shrimp trawl nets operating at 7 11 m depth in the Palk Bay, and Pamban-basedshrimp trawl nets operating in the Gulf of Mannar at 7-45 m depth, are presented. The catch per unit ofeffort in both the regions declined from 1986-87 to 1988 89. The spawning took place throughout the yearwith two peaks, one during July-September and the other during February-March. The overall growth rate,estimated from the modal progression in the monthly length frequency distribution, was 13.75 mm permonth for females (60-285 mm) and 12.3 mm per month for male (71 225 mm) in the Palk Bay. In the Gulfof Mannar it was 13.0 mm per month for female (86- 225 mm) and 10.0 mm per month for males (91 180mm). The differential growth between the sexes occurred as the prawns grew to 40-50 mm size.Males/females attained a size of 115/125 mm at the end of 6 months, 170/195 mm at 12 months, 215/250mm at 24 months and 230/270 mm at the end of 36 months in the Palk Bay. The corresponding male/femalesizes in the Gul I" of Mannar were 120/135 mm, 170/200 mm. 200/250 mm and 205/265 mm. The commercialfishery in both the regions was contributed by the 0-year group prawns. The total mortality rates in thepopulation exploited in these regions were relatively high, particularly for the male population. The stockin the fishing grounds considered at present is being subjected to over-exploitation.